The people of the book: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The People of the Book" refers to Jews and Christians in Islamic tradition, highlighting their shared belief in divine revelations. The term emphasizes the respect afforded to these groups due to their scriptures, which are acknowledged as containing truth. The narrative often explores themes of interfaith dialogue, the importance of understanding commonalities, and the call for mutual respect and coexistence among different religious communities. It encourages recognition of the shared values and ethical teachings found in these faiths.